Civilian Ballistic Tibia Shaft Fractures Compared With Blunt Tibia Shaft Fractures: Open or Closed?. Issue 3 (March 2021) - Prather, John C.; Montgomery, Tyler; Cone, Brent; Quade, Jonathan H.; Fellows, Kenneth; Devine, Thomas L.; Spitler, Clay A.
Abstract : Objectives: To identify a group of ballistic tibia fractures, report the outcomes of these fractures, and compare them with both closed and open tibia fractures sustained by blunt mechanisms. We hypothesized that ballistic tibia fractures and blunt open fractures would have similar outcomes. Design: Retrospective cohort study. Setting: A single Level-1 trauma center. Patients/Participants: Adult patients presenting with ballistic (44), blunt closed (179), or blunt open (179) tibia fractures. Intervention: Intramedullary stabilization of tibia fracture. Main Outcomes: Unplanned reoperation, soft tissue reconstruction, nonunion, compartment syndrome, and fracture-related infection. Results: Compared with the blunt closed group, the ballistic fracture group required more operations ( P < 0.01), had a higher occurrence of soft tissue reconstruction ( P < 0.01), and higher incidence of compartment syndrome ( P = 0.02). Ballistic and blunt closed groups did not significantly differ in rates of unplanned reoperation ( P = 0.67), nonunion (11.4% vs. 4.5%, P = 0.08), or deep infection (9.1% vs. 5.6%, P = 0.49). In comparison to the blunt open group, the ballistic group required a similar number of operations ( P = 0.12), had similar rates of unplanned reoperation ( P = 0.10), soft tissue reconstruction ( P = 0.56), nonunion (11.4% vs. 17.9%, P = 0.49), and fracture-related infection (9.1% vs. 10.1%, P = 1.0) but a higher incidence of compartment syndrome (15.9% vs. 5.0%, P = 0.02). Conclusions: Ballistic tibia fractures require more surgeries and have higher rates of soft tissue reconstruction than blunt closed fractures and seem to have outcomes similar to lower severity open fractures. We found a significantly higher rate of compartment syndrome in ballistic tibia fractures than both open and closed blunt fractures. When treating ballistic tibia fractures, surgeons should maintain a high level of suspicion for the development of compartment syndrome and counsel patients that ballistic tibia fractures seem to behave like an intermediate category between closed and open fractures sustained through blunt mechanisms. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.